Criminal offence domestic violence: Legal practice in Niš area - Vilić-Konstantinović Slobodanka; Petrušić Nevena (Temida, 2003)
In this paper authors analyze seven cases of domestic violence in Niš area during one year of implementation of the new criminal offence domestic violence. Using the method of indirect observation and interviews, authors give us an overview of police's, prosecutors and court's intervention in domestic violence cases. In spite of small number of registered and processed domestic violence cases, some negative phenomenons are observed. Those phenomenons unable efficient and accurate preventive and repressive actions toward abuser. Majority of these observed facts are noted and explained, with underlining the consequences and a way for overcoming them. In order to reach valid and scientifically based conclusion about implementation of laws regarding domestic violence, it is essential to undertake extensive research in Serbia, including a research of a practice of the police, prosecutors and courts. Results of such research would allow qualitative theoretical overview of law enforcement practice regarding domestic violence. Knowledge gained in this way would help us to establish programs for education of individuals who, in different roles, participate in preventive and repressive actions against domestic violence.